Shedding Skins : Four Sioux Poets - Schweigman, Kurt; Waters, Joel; Pacheco, Steve; Brings Plenty, Trevino L. (Book collections on Project MUSE., 2008)
From the Publisher: These poets are bound by a common attitude as well as a common heritage. All four--Joel Waters, Steve Pacheco, Kurt Schweigman (who writes under the name Luke Warm Water), and Trevino L. Brings Plenty--are Sioux, and all four identify themselves as "Skins" (as in "Redskins"). In their poems, they grapple with their heritage, wrestling with what it means to be a Sioux and a Skin today. It's a fight to the finish.